Perspectives on Defense Systems Analysis - Delaney (MIT Press, 2015)
Monograph
fulltext
Keywords: Aerospace; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Transportation; Signal Processing and Analysis